THE ROLE OF PUBLIC INSTITUTIONS IN TRAINING OF INTERNATIONAL RELATIONS SPECIALISTS IN CANADA - Kateryna Istomina (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with theoretical and pedagogical research of the development and integration of students' public work on the example of the system of professional training of future specialists on international relations in universities of Canada. The features of the organization have been analized and the implementation of students' public work into curricula of education programs has been done. This research provides general overview of factors that have direct impact on the successful integration of students' public work in the learning process and which depend on the success of this teaching method implementation. The difficulties of implementing students' public work in the learning process, as well as positive changes which is the result of this practice in higher education have been shown. The integration of public work in the system of professional training of specialists has been determined as the prospect of the development of higher education which promotes the individual formation with the necessary set of significant social, leadership and personal qualities. The prospects for further research in this area and the practical application of the results have been outlined.